Students' Pedagogical and Technical Challenges in Online Learning - Novriansyah, Alfie; Lasito, Lasito (Foremost Journal, 2022)
The advancement of the internet and the accessibility of technology has led to the development of online learning. Especially in this pandemic situation, students are forced to attend online learning despite their readiness. This study then aimed to explore the challenges faced by students of the English Language Study Program when attending online learning. This study used a descriptive qualitative method. The researcher gained the data by distributing questionnaires to students of the English Language Study Program from three universities in Jakarta, which are Universitas Negeri Jakarta, Universitas Muhammadiyah Prof. DR. Hamka, and Universitas Pamulang. The findings revealed that the students are facing the challenges in both pedagogical challenges and technical challenges. One of the challenges in pedagogical challenges is the results of students' work are not optimal due to a large number of assignments and lack of allocated time. While in technical categories, one of the challenges is the internet speed which is mostly slow due to bad weather or bad providers.